Administrasi oral imunostimulan ragi roti (Saccharomyces cerevisiae) untuk meningkatkan pertumbuhan ikan mas (Cyprinus Carpio L.) - Razak, Atiek P.; Kreckhoff, Reni L.; Watung, Juliaan Ch. (e-Journal BUDIDAYA PERAIRAN, 2017)
The research aimed to evaluate the effect of baker’s yeast as immunostimulant on the growth of carp.  Fish was obtained from Board of Freshwater Aquaculture at Tatelu, North Sulawesi Province.  Before running the experiment, the fish was acclimatized for one week in five concrete tanks measuring 2x1x1 m3 each. During acclimatization, fish was fed commercial pellet at 5%/body weight/day, twice a day.  After acclimatizationm, the fish was distributed in 15 aquaria with a density of 25 individuals per aquarium.  The research used Complete Randomized Design with five treatments namely 0, 5, 10, 15, and 20 g yeast/kg of pellet, each with three replications.  Fish was fed with treatment pellets for three weeks consecutively at a dose of 5%/body weight/day, twice a day at 08.00 am and 16.00 pm. Growth of fish was measured at the end of feeding period.  The result showed that the addition of baker’s yeast cells into fish feed significantly influenced fish growth. The best growth was achieved in fish fed pellet supplemented with 5 g yeast/kg of pellet.Keywords : Cyprinus carpio, Saccharomyces cerevisiae, immunostimulant, growth